Multi-slice coronary computed tomography angiography in assessment of coronary artery disease on the basis of syntax score - Amira Abd El-Ghany Khedr; Mohammed Fathy Dawoud; Al-Siagy Ali Salama; Taymour Moustafa Abd Allah; Basma Samir El-Deeb (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background The SYNTAX score (SS) was created to aid the Heart Team in assessing the severity and extent of coronary artery disease (CAD) in patients with multi-vessel disease, hence helping in the decision between percutaneous coronary intervention (PCI) and coronary artery bypass graft (CABG). SS is an important tool that assesses the angiographic complexity of the CAD based on Invasive coronary angiography (ICA). The study aims to evaluate the role of coronary Multi-Slice Computed Tomography (MSCT) angiography in the assessment of CAD on the basis of SS. Results Our study involved 60 patients with a male to female ratio 78.4% to 21.6%. The mean age of the patients was 57 years. Then, we applicate SYNTAX score II (SS-II) by incorporating a combination of SS-I and clinical variables. MSCT findings were compared with the data collected by cardiac catheterization. SYNTAX scores produced from coronary CT-angiography (CCTA) and those derived from ICA are concordant (P = 0.001). Direct correlation and significant relationship between SS-II for PCI and the mortality rate with the CT-derived SS-I. There was an inverse relationship between the CT-derived SS-I and SS-II for CABG. There was an inverse relationship between the CT-derived-SS with CABG mortality rate. Conclusions MSCT is a noninvasive imaging modality that has a significant value and high diagnostic accuracy compared to ICA in the evaluation of the complexity of CAD using SS and can be applied in clinical practice to determine the most convenient treatment procedure and predict long-term prognosis.